Trade Openness and Indonesia's Economic Growth: Empirical Evidence of the Role of Exports and Imports in Gross Domestic Product - Noldin Jerry Tumbel (Advances in Business & Industrial Marketing Research, 2026)
Purpose: This study examines the effects of exports and imports, as indicators of trade openness, on Indonesia’s real Gross Domestic Product (GDP) in both the short run and the long run. Research Method: Quarterly data from the first quarter of 2015 to the first quarter of 2026 (45 observations) were obtained from Statistics Indonesia. The study employs the Autoregressive Distributed Lag (ARDL) approach, including descriptive statistics, Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) unit root tests, lag selection using the Akaike Information Criterion (AIC), bounds testing, and short-run dynamic estimation. Results and Discussion: The results show that all variables are non-stationary at level but none is integrated of order two, validating the use of the ARDL model. The optimal specification is ARDL (1,4,1). The bounds test produces an F-statistic of 1.737, below the 5% lower critical bound (4.135), indicating no long-run equilibrium relationship between trade openness and real GDP. Moreover, exports and imports have no statistically significant short-run effects on economic growth. In contrast, significant second- and third-quarter dummy variables reveal seasonal patterns in GDP fluctuations, suggesting that aggregate trade values alone do not sufficiently explain economic growth. Implications: Trade policies should prioritize increasing domestic value added, improving productivity, and strengthening industrial linkages rather than merely expanding trade volumes. Originality: This study provides recent evidence on the trade openness–growth nexus in Indonesia using post-2015 quarterly data and demonstrates the limited explanatory power of aggregate trade flows in the absence of stronger domestic productive capacity.